2020
DOI: 10.18008/1816-5095-2020-3-519-526
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Personal Respiratory and Visual Protective Equipment on the Development and Progression of Dry Eye Syndrome

Abstract: Purpose. To study the influence of personal protective equipment (PPE) of the respiratory and visual systems on the development and progression of dry eye syndrome (DES) and its relationship with other risk factors for medical workers.Patients and methods. The data of 243 people (male — 22.2 %, female — 77.8 %) were analyzed as part of a multi-center analytical scientific one-step study. Total tear production (Schirmer I test) was studied at the beginning and the end of the working day in persons used PPE of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Among respiratory protective gear such as half-closed or closed glasses, protective screens, disposable face masks, or respirators, users have significantly impacted tear production during the pandemic period. Mask wear for 8 hours has reduced the Schirmer's values by 3mm [29]. In a study, the type of mask wear and duration of mask wear also showed similar results.…”
Section: Discussionmentioning
confidence: 69%
“…Among respiratory protective gear such as half-closed or closed glasses, protective screens, disposable face masks, or respirators, users have significantly impacted tear production during the pandemic period. Mask wear for 8 hours has reduced the Schirmer's values by 3mm [29]. In a study, the type of mask wear and duration of mask wear also showed similar results.…”
Section: Discussionmentioning
confidence: 69%
“…Reduced tear quantity after wearing respiratory PPE, including facemasks and respirators, is also seen. Schirmer's values reduced by 3mm after 8 hours of PPE usage [18].…”
Section: Discussionmentioning
confidence: 88%
“…Improper and prolonged wearing of masks/respirators causes an uneven distribution of exhaled warm air and increase in the evaporation of tear fluid from the ocular surface [66]. This mechanism of DES development is similar to the mechanism underlying constant positive airway pressure (CPAP) therapy, which results in augmented tear evaporation, eye irritation, and squamous metaplasia of the conjunctiva [67].…”
Section: Figure 1 Schematic Representation Of the Pathogenesis Of Cov...mentioning
confidence: 99%